MUC5B expression and location in surfactant protein C mutations in children. Issue 12 (7th April 2015) - Liptzin, Deborah R.; Watson, Alan M.; Murphy, Elissa; Kroehl, Miranda E.; Dishop, Megan K.; Galambos, Csaba; Evans, Christopher M.; Schwarz, Marvin I.; Deterding, Robin R.; Schwartz, David A.
Summary: Background: Mutations in Surfactant Protein C ( SFTPC ) can lead to fibrotic interstitial lung disease (ILD) with variable phenotypes, especially in children. The sources of phenotype variability are incompletely understood. A common MUC5B promoter variant rs35705950 is associated with adult Idiopathic Pulmonary Fibrosis (IPF). We examined whether MUC5B is similarly linked to ILD secondary to SFTPC mutations. Methods: MUC5B concentration in bronchoalveolar lavage fluid (BALF) was measured in six pediatric patients with SFTPC mutations and diseased controls. Immunohistochemical localization of MUC5B was studied in fixed lung tissues in patients with SFTPC mutations, ABCA3 mutations, and controls. Genotyping for the MUC5B promoter variant rs35705950 was attempted in all samples. Results: MUC5B glycoprotein was increased in BALF of patients with SFTPC mutations compared to diseased controls ( P = 0.04). MUC5B was unexpectedly present in cells morphologically consistent with alveolar epithelial type II cells in patients with SFTPC mutations in the BRICHOS domain. Genotyping for the MUC5B promoter variant was successful in 18/27 patients, and there was no significant relationship between the MUC5B promoter variant and the BALF or MUC5B localization. Conclusion: MUC5B may play a role in the development of fibrosis in patients with SFTPC mutations, especially in patients with BRICHOS mutations. Understanding the role of MUC5B in adult and pediatric lung diseases may lead to a better understanding of the etiology of fibrotic lung disease as well as development of novel therapies.Pediatr Pulmonol. 2015; 50:1270–1276. © 2015 Wiley Periodicals, Inc.